Managing Workflow Malleability in Urgent Computing for Earthquake Alerts - Ejarque, Jorge; Monterrubio-Velasco, Marisol; Bhihe, Cedric; Pienkowska, Marta; De La Puente, Josep; Badia, Rosa M. (SC24-W: Workshops of the International Conference for High Performance Computing, Networking, Storage and Analysis, 2024)
When large earthquakes happen, first responders need fast and accurate information regarding their impact. UCIS4EQ is an urgent computing platform that estimates ground shaking based on high-performance parallel 3D simulations. In this work, we present the PyCOMPSs implementation of UCIS4EQ towards urgent high-performance computing with a particular focus on providing a malleability mechanism. This allows UCIS4EQ to scan for data updates during runtime and dynamically incorporate said data into its execution. This involves, in particular, leveraging several HPC jobs. The implementation has been validated with data from the Samos Izmir earthquake. The malleable version of the workflow can reduce the use of computational resources by 40% while reducing the variability of the results and keeping the same time-to-solution as a non-malleable run.